Methodology Development in Directed Evolution: Exploring Options when Applying Triple‐Code Saturation Mutagenesis. (4th January 2018) - Qu, Ge; Lonsdale, Richard; Yao, Peiyuan; Li, Guangyue; Liu, Beibei; Reetz, Manfred T.; Sun, Zhoutong
Abstract: Directed evolution of stereo‐ or regioselective enzymes as catalysts in asymmetric transformations is of particular interest in organic synthesis. Upon evolving these biocatalysts, screening is the bottleneck. To beat the numbers problem most effectively, methods and strategies for building "small but smart" mutant libraries have been developed. Herein, we compared two different strategies regarding the application of triple‐code saturation mutagenesis (TCSM) at multiresidue sites of the Thermoanaerobacter brockii alcohol dehydrogenase by using distinct reduced amino‐acid alphabets. By using the synthetically difficult‐to‐reduce prochiral ketone tetrahydrofuran‐3‐one as a substrate, highly R ‐ and S ‐selective variants were obtained (92–99 % ee ) with minimal screening. The origin of stereoselectivity was provided by molecular dynamics analyses, which is discussed in terms of the Bürgi–Dunitz trajectory. Abstract : Directed evolution : Two strategies regarding the application of triple‐code saturation mutagenesis (TCSM) at multiresidue sites of the T. brockii alcohol dehydrogenase (TbSADH) by using distinct reduced amino‐acid alphabets are compared. By using prochiral tetrahydrofuran‐3‐one, highly R ‐ and S ‐selective variants are obtained with minimal screening. The origin of stereoselectivity is provided by molecular dynamics simulations.